THE ADDRESS FORMS OF JAMBINESE COMMUNITY IN SEBERANG KOTAJAMBI - yanti ismiyati (Jurnal Ilmiah Dikdaya, 2017)
The purpose of this research to find out liguistics phenomena and the reasons for the linguistic phenomena that happen in Jambinese forms in Jambinese community in Seberang Kota .The qualitative design is used in this research. The interview is used as the instrument to get the data concerning to the linguistics phenomena.There are four linguistics phenomena that happen to Jambinese forms in Seberang Kota classified as language maintance, language loss, language shift, and language change.based on the result od the research the Jambinesse address forms still exist until now.Eventhough the address forme of languge such as languag shift, language loss or language change is happend , the core of the Jambinesse address forms is still exist until now. Keywords: Language maintenance, Language loss, Language shift, Language change